Pengaruh Komitmen Beragama Dan Pengetahuan Agama Terhadap Komitmen Halal Dalam Kalangan Saudara Baru/ The Influence of Religious Commitment and Religious Knowledge on Halal Commitment among New Convert (UMRAN - Journal of Islamic and Civilizational Studies, 2026)
The halal industry is increasingly gaining recognition, not only among Muslims but also among non-Muslim communities. This trend reflects a growing demand for halal-certified products and services. The objective of this study is to examine the influence of religious commitment and religious knowledge on halal commitment among Muslim converts.This study employed a quantitative research design, with descriptive analysis used to explore the demographic profile of respondents, and inferential analysis specifically multiple regressionto identify the influence of religious commitment and religious knowledge (independent variables) on halal commitment (dependent variable).A total of 201 Muslim converts residing in the Kota Kinabalu area participated in the study by completing a structured questionnaire. The instruments used in this study included the Religious Knowledge Scale, the Muslim Daily Religiosity Assessment Scale (MUDRAS), and the Five-Component Customer Commitment Model.Data analysis was conducted using multiple regression via the Statistical Package for the Social Sciences (SPSS) version 27. The findings revealed that both religious knowledge and religious commitment did not significantly influence halal commitment among the respondents. The implications of the study suggest that efforts to introduce the concept of halal to Muslim converts must adopt a more comprehensive approach. Exposure should not be limited to the knowledge aspect alone but should also consider psychological factors and the social experiences of converts as they adapt to an Islamic way of life. Therefore, strategies to strengthen halal commitment among Muslim converts must be developed holistically, involving collaboration between communities, religious institutions, and industry stakeholders. Continuous support and easy access to credible halal information and products are essential to ensuring meaningful engagement with the concept of halal among this group.
Keywords: Halal commitment, religious knowledge, religiosity, Muslim converts